Childhood vs. juvenile absence epilepsy: How to make a diagnosis. (November 2022) - Asadi-Pooya, Ali A.; Farazdaghi, Mohsen
Highlights: 196 patients were studied. Generalized tonic-clonic seizure was reported by 134 patients (68.4%). The ROC curve of the age at seizure onset was an acceptable indicator to anticipate GTCS. The best cutoff point was at 9.65 years (age at onset). The odds ratio of the presence of GTCS in JAE compared with CAE was 3.6. Abstract: Purpose: We tried to differentiate childhood absence epilepsy (CAE) from juvenile absence epilepsy (JAE) based on their clinical characteristics. We planned to identify a cutoff point for the age at onset of seizures between CAE and JAE that is able to reliably predict the presence of generalized tonic-clonic seizures (GTCS) (that has important implications for treatment strategy and outcome prediction). Methods: This was a retrospective database study. All patients with an electro-clinical diagnosis of CAE or JAE were studied at the outpatient epilepsy clinic at Shiraz University of Medical Sciences, Shiraz, Iran, from 2008 until 2022. The receiver operating characteristic (ROC) curve was used for the statistical analysis to predict a cutoff point for the age at onset of seizures between the syndromes. Results: One hundred and ninety-six patients were studied. Generalized tonic-clonic seizure was reported by 134 patients (68.4%). The ROC curve of the age at seizure onset was an acceptable indicator to anticipate GTCS; the best cutoff point was at 9.65 years; 87 patients (44.4%) had CAE and 109 people (55.6%) had JAE. The odds ratio of the presence of GTCS in JAE compared with CAE was 3.6. Conclusion: Syndrome diagnosis of CAE vs. JAE has important practical implications. The age at onset of seizures serves as a reliable and meaningful variable to differentiate CAE from JAE.